ANALISIS DAN PERANCANGAN SISTEM INFORMASI E-COMMERCE PADA DISTRO SUCKSME STORE JAMBI - Saefudin, Saefudin; Siahaan, Kondar (Jurnal Manajemen Sistem Informasi, 2020)
Sucksme Store Distro is a sales shop that is engaged in fashion styles such as various kinds of T-shirts, shirts, pants, shoes, backpacks, etc., on the Sucksme Store Store has supporters in marketing their merchandise, because currently distro customers can only be visited visited by the shop to make product purchases, as well as product promotion by word of mouth, as well as long distance from the store location. Then designed an E-Commerce Information System at Sucksme Store Jambi Distro with the aim to facilitate product marketing, increase sales and reduce expenditure costs. In this study using prototyping modeling, it is expected that the results of this study provide customers to make purchases, bookings and payment confirmation. As well as administrators can manage item data, memeber data, ordering data and product purchases. For the future analysis and design of e-Commerce systems can be developed such as being able to exchange messages between potential buyers and managers of Sucksme Store Jambi Distro.